Prospects for predicting and preventing the heart failure deterioration: an analytical review - V. N. Larina; I. K. Skiba (Российский кардиологический журнал, 2024)
Heart failure (CHF) is a syndrome characterized by a progressive course with varying duration of stability period, frequent episodes of clinical deterioration, despite the therapy. HF deterioration often leads to repitalizations and poor prognosis. A possible reduction in rehospitalization rate and prognosis improvement by early administration of optimal therapy and modernization of non-drug approaches is an urgent area of research. An integrated approach using scales, algorithms and relevant therapy strategies can significantly improve treatment outcomes and quality of life in patients with HF.